Phenomenology of Consumer Satisfaction through Improving Service Quality in Kediri Banana Chips MSMEs Post Pandemic - Erwin Syahputra; Imam Mukhlis (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the phenomenology of consumer satisfaction through service quality at banana chips MSMEs in Kediri - East Java. Banana chips MSMEs consistently improve services, through information technology-based integrated services, creating productive human resources, encouraging digital transformation and sustainable innovation. In order to achieve this goal, the Kediri banana chips MSME seeks to improve the quality of service for consumers and customers in order to increase MSME income, one of the efforts to improve the welfare of its employees. There are 15 employees at this MSME with clear and transparent respective duties. The method used by these MSMEs in the last six months is to train their employees in dealing with consumers and support with technological knowledge as a tool used to promote products in a sustainable manner using existing e-commerce and social media. Survey service quality and consumer satisfaction through interviews, statements, star ratings along with constructive criticism and suggestions to increase MSME profits and consumer trust. There were 10 informants from the consumer side. Apart from getting feedback on the services provided, it can also be used as a means of providing information to the public as consumers. Using qualitative methods with a narrative phenomenological analysis model which is a description of the experiences of the informants.